87.2k views
5 votes
Question is in picture

User Lexk
by
4.8k points

1 Answer

3 votes

b)-3,\text{ -}(1)/(2)

Step-by-step explanation

The zero of a function is any replacement for the variable that will produce an answer of zero,so to find the zeros of this function we need set the equation = 0, and then solve for x


2x^2+7x+3=0

The rigth side of the equation is zero, so we can solve


\begin{gathered} 2x^2+7x+3=0\Rightarrow ax^2+bx+c \\ \end{gathered}

we can use the quadratic formula


\begin{gathered} x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ \text{replace} \\ x=\frac{-7\pm\sqrt[]{7^2-4\cdot2\cdot3}}{2\cdot2} \\ x=\frac{-7\pm\sqrt[]{49-24}}{4} \\ x=\frac{-7\pm\sqrt[]{25}}{4} \\ x=(-7\pm5)/(4) \end{gathered}

therefore.


\begin{gathered} x_1=(-7+5)/(4)=-(2)/(4)=-(1)/(2) \\ x_2=(-7-5)/(4)=-(12)/(4)=-3 \end{gathered}

so, the answer is


b)-3,\text{ -}(1)/(2)

I hope this helps you

User Agchou
by
4.6k points